RC: One of our tigers is missing! - Sue Graves (London, Franklin Watts, 2019)
Ted and Ava love everything about tigers, and are excited to visit the safari park. When they discover that one of the tigers is missing, their expert knowledge helps the ranger to track the tiger down. Reading Champion offers independent reading books for children to practise and reinforce their developing reading skills